2019
DOI: 10.3390/en12061071
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Using Biogas to Supply the Dual Fuel Diesel Engine of an Agricultural Tractor

Abstract: It is known that biogas without prior purification to biomethane is a commonly used fuel only for the stationary internal combustion engines but not for vehicle engines. The current study evaluates the use of biogas without its prior upgrading to biomethane as fuel for tractor engines. The following tests were carried out: biochemical methane potential tests, dynamometer engine tests, and field tests with the use of a tractor. The average methane content in biogas obtained from vegetable wastes exceeded 60%. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 40 publications
(33 reference statements)
1
14
0
Order By: Relevance
“…Similar decreases in PM emission for biogas-diesel fuels were reported by H.S. Tira [59] and Owczuk et al [34].…”
Section: Model Validationsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar decreases in PM emission for biogas-diesel fuels were reported by H.S. Tira [59] and Owczuk et al [34].…”
Section: Model Validationsupporting
confidence: 86%
“…Lounici et al [33] reported that the high proportion of CO 2 present in biogas significantly reduces NO X and PM. Owczuk et al [34] found that biogas containing up to 50% CO 2 can be applicable as a tractor fuel.…”
Section: Introductionmentioning
confidence: 99%
“…The versatile use of biogas as well as the production of valuable bio-fertiliser will play a key role in the agricultural chain. However, there are ambiguous facets not clearly investigated, namely the case of multiple waste streams, microbiome, or end-products (Baek et al, 2018; Éles et al, 2019; Huang et al, 2017; Koç et al, 2019; Owczuk et al, 2019; Xu et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in some countries, such schemes are even expiring without successors being introduced. One of the applications might be the use of biomethane as transport fuel [41] because long-haul transport segments such as the maritime industry are hard to electrify in a short-to-medium term, and, as such, they offer an ideal destination for the valorisation of the available biogas streams [42]. Furthermore, the maritime industry will soon be included in the EU's climate action policies and regulations by which the demand for sustainable solutions will grow significantly.…”
Section: Resultsmentioning
confidence: 99%